Modeling and Experimental Study on Drying Characteristics of Corn Particles with Hot Air in Downward Moving Bed - Hairui Wang; Shuangming Zhang; Haodong Fan; Man Zhang; Nan Hu; Hairui Yang (Fluids, 2023)
With regard to drying fresh grain prior to storage, the drying tower with a downward moving bed with hot air is often used, which always has high energy consumption during operation. To optimize the operation, according to the actual operating parameters of a corn drying tower with hot air, a heat balance model was established, and the heat transfer between the hot air and corn flow in a downward moving bed was analyzed. Since the downward moving time is short, the heat absorbed by corn significantly depends on the heat transfer coefficient, mainly the convective heat transfer, between the hot air and corn surface. To determine the convective heat transfer coefficient, a hot air drying experimental system for corn grains was established, and the effects of hot air temperature and wind speed on the central temperature and moisture content of corn grains were analyzed. Utilizing the heat balance model, the convective heat transfer coefficients between corn particles and hot air were calculated. The total convective heat transfer coefficients are in the range of 39.4–53.8 W/m2 · K. With an average value of 46.7 W/m2 · K, drying energy efficiencies in different drying zones in the drying tower were calculated, and the accuracy of the model was verified by the operation data. Due to the high inlet temperature of hot air, the maximum energy efficiency of the first zone is 60.15%, whereas when the temperature of hot air in the second drying tower is 140 °C, the energy efficiency is only 41.97%. Therefore, under the premise of ensuring the drying rate, the temperature of hot air of the second zone should be appropriately reduced to improve the whole drying energy efficiency.